Justice, Expediency, and Legal Certainty in Indonesia's Constitutional Adjudication of the 2024 Presidential Election - Nanda Setya Darmawan (As-Siyasi: Journal of Constitutional Law, 2026)
This study examines the amendment to the eligibility requirements for presidential and vice-presidential candidates following Constitutional Court Decision Number 90/PUU-XXI/2023, which enabled the candidacy of Gibran Rakabuming Raka and generated constitutional debate concerning the principles of justice, expediency, and legal certainty in Indonesia's constitutional democracy. This research aims to: (1) analyze whether the amended eligibility requirements reflect these fundamental legal values; and (2) examine their implications for Indonesia's legal system. This study employs normative legal research using statutory and conceptual approaches. The analysis is conducted through qualitative legal reasoning based on primary, secondary, and tertiary legal materials, using Gustav Radbruch's theory of justice, expediency, and legal certainty as the analytical framework. The findings indicate that the Court's legal reasoning raises constitutional concerns regarding the balanced realization of these legal values. From the perspective of justice, the decision presents issues relating to equality of political opportunity and judicial impartiality. In terms of expediency, it has broader implications for democratic governance and political representation. Regarding legal certainty, the ruling reflects an expanded constitutional interpretation of the Court's authority in determining candidate eligibility requirements. The novelty of this study lies in applying Radbruch's triadic legal values as an integrated framework for evaluating constitutional adjudication in Indonesia. Theoretically, this study contributes to the development of constitutional adjudication scholarship through a value-based analytical model. Practically, it provides normative insights for strengthening judicial integrity, constitutional ethics, and legal certainty in future constitutional adjudication